Human development - Crandell, Thomas L.; Crandell, Corinne Haines; Vander Zanden, James Wilfrid (New York : McGraw-Hill, 2012)
Provides applications to psychology, health care, social work, education, and family dynamics. This title examines populations at risk and explains how they experience development and why their experience is different
1. The study of human development -- 2. Beginnings -- 3. Birth and infancy : the first two years -- 4. Early childhood -- 5. Middle childhood : 7 to 12 -- 6. Adolescence -- 7. Early childhood -- 8. Middle childhood -- 9. Late childhood -- 10. The end of life
Includes bibliographical references (p. 649-718) and index
Keywords: Developmental psychology -- Textbooks